Використання доповненої реальності в вищих закладах освіти в курсі фізики - Єрохіна, Д. С.; Кулішова, Н. Є. (ХНУРЕ, 2025)
This work is devoted to the use of augmented reality technology during studying the course of physics in higher education, designing and creating a three-dimensional model and animation of the physical process. The use of AR-technologies while reading theoretical material or conducting experiments, without the possibility of doing them in laboratories, is a value resource that enables applicants to visually understand how the process is going on, help teachers convey important information to students, and immerse them in studying the course.
Keywords: курс фізики; доповнена реальність